PROBLEM-BASED TASKS IN FOREIGN LANGUAGE ACQUISITION FOR INTENDING EDUCATORS - Dmitrenko, Natalia; Petrova, Anastasiia; Podzygun, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The problem-based learning of a foreign language is aimed to develop students’ creativity, increase their motivation, autonomy, experience future profession tasks, and improve cognitive and communicative skills. The purpose of the article is to justify the efficiency of forming communicative skills of intending educators by means of problem-based tasks within the discipline “English for Professional Communication”. The objective of the article is to report about the results of using problem-based tasks in students’ acquisition of course content and in formation of students’ linguistic competence. In order to test the theoretical statements of using problem-based tasks in foreign language acquisition, a diagnostic experimental study was conducted. It was aimed at identifying cognitive-communicative needs and opportunities of students in solving problem tasks. The study included: experimental training, diagnostic tests and questionnaires for students and teachers. As a result, the cognitive and communicative needs and opportunities of students to solve problem tasks were determined; the prospects of application of problem tasks in the development of creative thinking in the process of formation and development of skills of foreign language communication were revealed. The experiment data enable to conclude that regular using of problem-based tasks marked positive impact on formation of students’ linguistic competence. Phonetic, lexical and grammatical skills have improved due to communication with peers and self-control during solving problem tasks. The overall results of the study affirm the enhancement of students’ speaking skills (monologue, dialogue, polylogue skills).